Positive electrode material and preparation method and application thereof

By introducing carbon cladding and transition metal doping elements into the NFPP material, combined with multi-stage sintering treatment and spray drying technology, a positive electrode material with excellent conductivity was prepared, which solved the problem of poor conductivity of NFPP material and improved the charge and discharge capacity and electrochemical performance of the battery.

CN119812263APending Publication Date: 2025-04-11NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411978848.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The iron-based polyanionic material Na4Fex(PO4)2P2O7(NFPP) has poor intrinsic conductivity, which limits its application in sodium ion batteries.

Method used

By introducing a carbon cladding layer into the NFPP material, a NaxFeyMZBa(PO4)2(P2O7) structure is formed, where M is a transition metal doping element, and combined with multi-stage sintering treatment and spray drying technology, a positive electrode material with excellent conductivity was prepared.

Benefits of technology

It improves the charge and discharge capacity and electrochemical performance of the battery, enhances the conductivity and stability of the cathode material, and is suitable for large-scale production and application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812263A_ABST
    Figure CN119812263A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode material as well as a preparation method and application thereof. The positive electrode material comprises an inner core and a carbon coating layer coating at least part of the surface of the inner core, the molecular formula of the inner core is NaxFeyMZBa (PO4) 2 (P2O7); m is a transition metal doping element; 3.8 < = x < = 4.2, 2.5 < = y < = 3, 0 < = z < = 0.5, 0.00001 < = a < = 0.0005; in the phase composition of the inner core, the mass percentage content of Na4Fex( PO4) 2P2O7 is greater than or equal to 89%, the mass percentage content of NaFePO4 is 1-8%, the mass percentage content of Na2FeP2O7 is 2-9%, and the mass percentage content of NaFe (P2O7) is 0.2-1.5%; in the positive electrode material, the mass percentage of the carbon coating layer is 1-5%. The positive electrode material has excellent conductivity, and can improve the charge-discharge capacity of the battery when being applied to the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a positive electrode material and a preparation method and application thereof, belonging to the technical field of secondary batteries. Background Art

[0002] In sodium-ion batteries, the cathode material is one of the main factors affecting the overall electrochemical performance of sodium-ion batteries. The cathode material determines the battery's energy density, cycle stability, interface compatibility and other properties. Common cathode materials include layered oxides, Prussian cathode materials and polyanion cathode materials. Compared with layered oxides and Prussian cathode materials, polyanion cathode materials are more widely concerned by the market due to their stable framework structure of ionic groups, higher electrochemical stability and wider operating temperature range.

[0003] Iron-based polyanion material Na 4 Fe x (PO 4 ) 2 P 2 O 7 (NFPP) has attracted widespread attention due to its low cost, low toxicity, simple preparation process and greater suitability for large-scale production. However, NFPP material has poor intrinsic conductivity, which is not conducive to the application of NFPP material. Summary of the invention

[0004] The invention provides a positive electrode material, which has excellent conductivity and can improve the charge and discharge capacity of a battery when applied to the battery.

[0005] The present invention provides a preparation method for preparing the positive electrode material. The preparation method is simple to operate and is suitable for wide promotion and application.

[0006] The present invention provides a battery, comprising the positive electrode material, and the battery has excellent charge and discharge capacity.

[0007] The present invention provides a positive electrode material, wherein the positive electrode material comprises a core and a carbon coating layer coated on at least a portion of the surface of the core;

[0008] The molecular formula of the core is shown in Formula 1;

[0009] Na x Fe y M Z B a (PO 4 ) 2 (P 2 O 7 ) Formula 1;

[0010] Wherein, M is a transition metal doping element;

[0011] 3.8≤x≤4.2, 2.5≤y≤3, 0≤z≤0.5, 0.00001≤a≤0.0005;

[0012] The phase composition of the inner core includes Na 4 Fe x (PO 4 ) 2 P 2 O 7 、NaFePO 4 、Na 2 FeP 2 O 7 and NaFe(P 2 O 7 ), and in the phase composition of the core, Na 4 Fe x (PO 4 ) 2 P 2 O 7 The mass percentage of NaFePO is ≥89%, 4 The mass percentage of Na is 1-8%, 2 FeP 2 O 7 The mass percentage of NaFe(P 2 O 7 ) has a mass percentage of 0.2-1.5%;

[0013] In the positive electrode material, the mass percentage of the carbon coating layer is 1-5%.

[0014] The positive electrode material as described above, wherein the moisture content of the positive electrode material is ≤1000ppm.

[0015] The positive electrode material as described above, wherein D50 of the positive electrode material is 2-15 μm.

[0016] The positive electrode material as described above, wherein the thickness of the carbon coating layer is 3-4 nm.

[0017] The positive electrode material as described above, wherein in the unit cell of the positive electrode material, the length of the a-axis is The length of the b axis is The length of the c-axis is and / or,

[0018] The unit cell volume of the positive electrode material is

[0019] The present invention provides a method for preparing the positive electrode material as described above, which comprises the following steps:

[0020] A raw material system including a sodium source, an iron source, a carbon source, a boron source, and a phosphorus source or a raw material system including a sodium source, an iron source, a carbon source, a boron source, a phosphorus source, and an M source is subjected to sand milling to obtain a spray slurry having a D50 of 0.25-0.35 μm;

[0021] spray drying the spray slurry to obtain spray particles;

[0022] Sintering the spray particles to obtain the positive electrode material;

[0023] The sintering process at least includes a first sintering process, a second sintering process, and a third sintering process, and the temperature of the first sintering process, the temperature of the second sintering process, and the temperature of the third sintering process increase in sequence.

[0024] The preparation method as described above, wherein in the first sintering treatment, the temperature is 160-200° C. and the time is 2-5 h; and / or,

[0025] In the second sintering treatment, the temperature is 430-500° C. and the time is 10-16 hours; and / or,

[0026] In the third sintering treatment, the temperature is 520-580° C. and the time is 2-6 hours.

[0027] The preparation method as described above, wherein in the sand grinding treatment, the sand grinding speed is 1200-1600 r / min, and the time is 250-400 min.

[0028] In the preparation method as described above, in the spray drying process, the inlet air temperature is 170-190° C., the outlet air temperature is 80-100° C., and the feed speed is 30-50 rpm.

[0029] The present invention provides a battery, comprising the positive electrode material as described above.

[0030] The special composition and structure of the positive electrode material of the present invention enable it to improve the electrochemical performance of the battery when applied to the battery, for example, it can improve the charge and discharge capacity of the battery.

[0031] The present invention provides a method for preparing a positive electrode material, which can prepare the positive electrode material mentioned above. The preparation method is simple to operate and is suitable for wide promotion and application.

[0032] The present invention provides a battery, comprising the positive electrode material, so the battery has excellent electrochemical properties, for example, excellent charge and discharge capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or related technologies, the following briefly introduces the drawings required for use in the embodiments of the present invention or related technologies. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0034] Figure 1 This is a surface SEM image of the positive electrode material in Example 1 of the present invention;

[0035] Figure 2 This is a cross-sectional SEM image of the positive electrode material in Example 1 of the present invention;

[0036] Figure 3 This is a cross-sectional SEM image of the positive electrode material in Comparative Example 3 of the present invention;

[0037] Figure 4 This is a cross-sectional C element distribution diagram of the positive electrode material in Example 1 of the present invention;

[0038] Figure 5 This is a cross-sectional Fe element distribution diagram of the positive electrode material in Example 1 of the present invention;

[0039] Figure 6 This is a cross-sectional P element distribution diagram of the positive electrode material in Example 1 of the present invention;

[0040] Figure 7 This is a cross-sectional Na element distribution diagram of the positive electrode material in Example 1 of the present invention;

[0041] Figure 8 This is a cross-sectional B element distribution diagram of the positive electrode material in Example 1 of the present invention;

[0042] Fig. 9 is the XRD diagram of the positive electrode material in Example 1 of the present invention;

[0043] Fig.10 The charge and discharge curves of the battery prepared by the positive electrode materials in the embodiments of the present invention and the comparative examples;

[0044] Fig.11 Graphs showing ion diffusion coefficients in the charging phase of batteries prepared from the positive electrode materials in Example 1 and Comparative Example 3 of the present invention;

[0045] Fig.12 Graph showing the ion diffusion coefficient of the discharge stage of the battery prepared from the positive electrode materials in Example 1 and Comparative Example 3 of the present invention;

[0046] Fig.13 Electrochemical impedance spectra of batteries prepared with the positive electrode materials in Example 1 and Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0047] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] A first aspect of the present invention provides a positive electrode material, the positive electrode material comprising a core and a carbon coating layer coated on at least a portion of the surface of the core;

[0049] The molecular formula of the core is shown in Formula 1;

[0050] Na x Fe y M Z B a (PO 4 ) 2 (P 2 O 7 ) Formula 1;

[0051] Wherein, M is a transition metal doping element;

[0052] 3.8≤x≤4.2, 2.5≤y≤3, 0≤z≤0.5, 0.00001≤a≤0.0005;

[0053] The phase composition of the inner core includes Na 4 Fe x (PO 4 ) 2 P 2 O 7 、NaFePO 4 、Na 2 FeP 2 O 7 and NaFe(P 2 O 7 ), and in the phase composition of the inner core, Na 4 Fe x (PO 4 ) 2 P 2 O 7 The molar percentage of NaFePO is ≥89%, 4 The molar percentage is 1-8%, Na 2 FeP 2 O 7 The molar percentage is 2-9%, NaFe(P 2 O 7) has a molar percentage of 0.2-1.5%;

[0054] In the positive electrode material, the mass percentage of the carbon coating layer is 1-5%.

[0055] In the present invention, the carbon coating layer can be coated on the entire surface of the core, or on a portion of the surface of the core. The carbon coating layer can improve the conductivity of the positive electrode material on the one hand, and on the other hand, it can protect the core, prevent the core from absorbing moisture due to excessive contact with air, and improve the stability of the positive electrode material.

[0056] The core of the present invention is a polyanion compound including at least Na, Fe, B, P, and O. In some embodiments, the core may also include an M element, where M is a transition metal doping element. For example, M may be at least one of Al, Ni, Co, Mn, Cu, Ti, V, and Zr.

[0057] In the present invention, the positive electrode material can be subjected to an XRD test to obtain the XRD spectrum of the positive electrode material, and then the XRD spectrum is refined to obtain the phase composition of the core and the Na 4 Fe x (PO 4 ) 2 P 2 O 7 、NaFePO 4 、Na 2 FeP 2 O 7 and NaFe(P 2 O 7 The positive electrode material can be subjected to thermogravimetric analysis to obtain the mass percentage of the carbon coating layer in the positive electrode material.

[0058] In the positive electrode material of the present invention, the boron element has a unique electron-deficient property, and the boron ion has the characteristic of releasing electrons, which helps to improve the electronic conductivity of the positive electrode material. In addition, the boron element can also reduce the sintering temperature, thereby facilitating the sintering of the NFPP material, increasing the content of NFPP in the kernel, and thus improving the capacity and structural stability of the positive electrode material. And because the boron-oxygen bond energy is larger than the phosphorus-oxygen bond, it is more conducive to maintaining the phase stability of the positive electrode material. At the same time, when the positive electrode material also includes the M element, the high entropy doping method can further improve the structural stability of the positive electrode material, thereby facilitating the rapid transmission of sodium ions inside the positive electrode material. A specific content of the carbon coating layer can further improve the conductivity and stability of the positive electrode material while ensuring the electrochemical properties of the positive electrode material.

[0059] In some embodiments of the present invention, the moisture content of the positive electrode material is ≤1000 ppm.

[0060] In the present invention, the moisture content of the positive electrode material can be tested by the Karl Coulometry method. When the moisture content of the positive electrode material is ≤1000ppm, the stability of the positive electrode material can be further improved, thereby improving the cycle performance of the battery.

[0061] In some embodiments of the present invention, the D50 of the positive electrode material is 2-15 μm.

[0062] The D50 of the positive electrode material refers to the D50 of the secondary particles formed by the positive electrode material. When the D50 of the positive electrode material meets the above range, the positive electrode material is not easy to break when applied to the battery, which helps to improve the cycle performance of the battery, and the positive electrode material has excellent kinetic properties, which helps to improve the rate performance of the battery.

[0063] Since the positive electrode material of the present invention includes a core and a carbon coating layer, the present invention can also select specific parameters of the carbon coating layer to further improve the comprehensive performance of the positive electrode material.

[0064] In some embodiments of the present invention, the thickness of the carbon coating layer is 3-4 nm.

[0065] Among them, the thickness of the carbon coating layer refers to the average thickness of the carbon coating layer. In some embodiments of the present invention, a transmission electron microscope (TEM) can be used to test the positive electrode material, obtain a TEM image of the positive electrode material, and obtain the thickness of the carbon coating layer according to the TEM of the positive electrode material. When the thickness of the carbon coating layer meets the above range, the conductivity of the positive electrode material can be further improved while ensuring the electrochemical properties of the positive electrode material, and the inner core can be better protected to prevent the inner core from absorbing moisture due to excessive contact with the air, thereby further improving the stability of the positive electrode material.

[0066] In some embodiments of the present invention, in the unit cell of the positive electrode material, the length of the a-axis is The length of the b axis is The length of the c-axis is and / or,

[0067] The unit cell volume of the cathode material is When the ion transport capacity of the battery is improved, the electrochemical performance of the battery can be improved.

[0068] A second aspect of the present invention provides a method for preparing a positive electrode material, comprising the following steps:

[0069] A raw material system including at least a sodium source, an iron source, a carbon source, a boron source, and a phosphorus source or a raw material system including at least a sodium source, an iron source, a carbon source, a boron source, a phosphorus source, and an M source is subjected to sand milling to obtain a spray slurry having a D50 of 0.25-0.35 μm;

[0070] The spray slurry is spray-dried to obtain spray particles with a D50 of less than 10 μm;

[0071] The spray particles are sequentially sintered to obtain positive electrode materials;

[0072] The sintering process at least includes a first sintering process, a second sintering process, and a third sintering process, and the temperature of the first sintering process, the temperature of the second sintering process, and the temperature of the third sintering process increase in sequence.

[0073] Specifically, a sodium source, an iron source, a carbon source, a boron source, and a phosphorus source may be mixed and then stirred and dissolved in deionized water to obtain a raw material system. Alternatively, a sodium source, an iron source, a carbon source, a boron source, a phosphorus source, and a phosphorus source may be mixed and then stirred and dissolved in deionized water to obtain a raw material system.

[0074] Then, the raw material system is subjected to sand grinding treatment to form a spray slurry with a D50 of 0.25-0.35 μm, and then the spray slurry is subjected to spray drying treatment to obtain spray particles with a D50 of less than 10 μm;

[0075] Finally, the spray particles are subjected to at least a low-temperature first sintering treatment, a medium-temperature second sintering treatment, and a high-temperature third sintering treatment, so as to obtain a positive electrode material.

[0076] It can be understood that the sintering process of the present invention includes at least three sintering processes, and may also include multiple sintering processes (≥3 times). The present invention can further select the number of sintering processes according to actual needs. Exemplarily, the sintering process may also include a fourth sintering process and a fifth sintering process, and the temperature of the first sintering process, the temperature of the second sintering process, the temperature of the third sintering process, the temperature of the fourth sintering process, and the temperature of the fifth sintering process increase in sequence.

[0077] In some embodiments, in the raw material system, the ratio of the molar content of Na element in the sodium source, the molar content of Fe element in the iron source, and the molar content of P element in the phosphorus source is 4:(2.5-3):4, the doping amount of boron element in the boron source is ≤2000ppm, the doping amount of M element in the M source is 0-50000ppm, and the mass percentage of the carbon source is 5-15%.

[0078] In some embodiments, the solid content of the raw material system can be 0.2-0.4wt%, and the raw material system belongs to the kilogram-level sample preparation; the sand grinding treatment can be carried out in a vertical or horizontal sand mill; a spray dryer can be used for spray drying treatment; the first sintering treatment, the second sintering treatment and the third sintering treatment can be carried out in a tubular furnace, and the tubular furnace is evacuated and nitrogen or inert gas is passed through for three cycles.

[0079] The present invention does not specifically limit the sodium source, and the sodium source can be a compound containing sodium commonly used in the art. For example, the sodium source can be one or more of sodium pyrophosphate, sodium hydrogen phosphate, and sodium dihydrogen phosphate. The present invention does not specifically limit the iron source, and the iron source can be a compound containing iron commonly used in the art. For example, the iron source can be one or more of ferric phosphate, ferric oxide, ferric acetate, and ferric citrate. The present invention does not specifically limit the phosphorus source, and the phosphorus source can be a compound containing phosphorus commonly used in the art. For example, the phosphorus source can be one or more of ferric phosphate, sodium phosphate, and sodium dihydrogen phosphate. The present invention does not specifically limit the carbon source, and the phosphorus source can be one or more of ferric phosphate, sodium phosphate, and sodium dihydrogen phosphate. The boron source is not particularly limited, as long as the compound can form carbon after high-temperature sintering, it belongs to the protection scope of the present invention. For example, the carbon source can be one or more of glucose, citric acid, ascorbic acid and polyethylene glycol; the boron source is not particularly limited in the present invention, and the boron source can be a compound containing the boron element commonly used in the art. For example, the boron source can be at least one of boron oxide, boric acid and sodium borate; the M source is not particularly limited in the present invention, and the M source can be a compound containing the M element commonly used in the art. For example, the M source can be at least one of oxides of metal elements from Group III to Group V and organic acid salts.

[0080] In the preparation method of the present invention, the sintering treatment includes a first sintering treatment, a second sintering treatment, and a third sintering treatment with successively increasing temperatures, wherein the first sintering treatment with the lowest temperature can promote uniform dispersion of the carbon source, which is beneficial to the formation of the carbon coating layer in the subsequent second sintering treatment and the third sintering treatment, and can not only improve the electrochemical performance of the positive electrode material, but also make the structure of the positive electrode material more stable, improve the safety performance of the positive electrode material, and thus improve the comprehensive performance of the battery. At the same time, the present invention adopts multi-stage temperature for sintering treatment, which can also promote the formation of NFFP phase in the positive electrode material, promote the uniform distribution of B element and / or M element in the lattice of the inner core, and further improve the electrochemical performance of the positive electrode material.

[0081] It is worth mentioning that in the preparation method of the present invention, the raw materials are cheap and easily available, the operation is simple, and it is conducive to actual large-scale mass production.

[0082] Furthermore, when the temperature is 160-200°C and the time is 2-5h in the first sintering treatment, the uniform dispersion of the carbon source can be further promoted, thereby promoting the formation of a carbon coating layer in the subsequent sintering process, and effectively improving the electronic conductivity of the positive electrode material. For example, the charge and discharge capacity of kilogram-level positive electrode materials is above 100mAh / g.

[0083] When the temperature is 430-500° C. and the time is 10-16 h in the second sintering treatment, the formation of the carbon coating layer can be further promoted, the coating uniformity of the carbon coating layer can be improved, and the electrochemical performance and stability of the positive electrode material can be improved.

[0084] When the temperature is 520-580° C. and the time is 2-6 hours in the third sintering treatment, a uniform carbon coating layer can be further formed to obtain a positive electrode material with excellent electrochemical performance and excellent structural stability.

[0085] In some embodiments, the tube furnace may be heated from room temperature to a temperature required for a first sintering process at a certain heating rate, the first sintering process may be performed, and then the tube furnace may be heated from the temperature of the first sintering process to the temperature required for a second sintering process at a certain heating rate, and then the tube furnace may be heated from the temperature of the second sintering process to the temperature required for a third sintering process at a certain heating rate. Further, the heating rate may be 3-5°C / min.

[0086] In some embodiments of the present invention, when the sand milling speed is 1200-1600r / min and the time is 250-400min, the raw material system can be sand milled into a spray slurry with a more uniform target particle size, which promotes the subsequent process and improves the comprehensive performance of the positive electrode material. In some embodiments, after sand milling, a spray slurry with D50 < 0.3μm can be obtained.

[0087] In some embodiments of the present invention, when the air inlet temperature is 170-190°C and the air outlet temperature is 80-100°C during the spray drying process, the spray slurry can be dried more efficiently to obtain spray particles of the target particle size, promote the subsequent sintering process, obtain a positive electrode material with a lower moisture content, and thus improve the overall performance of the positive electrode material. In some embodiments, the feed rate of the spray drying process can be 30-50 rpm.

[0088] In some embodiments, a post-treatment is also included after the third sintering treatment, and the post-treatment includes moving the system after the third sintering treatment to a jet mill for crushing treatment to make the D50 of the sintered material less than 5μm, and then performing drying, batch mixing and iron removal processes to obtain a positive electrode material with a higher purity and a specific particle size.

[0089] A third aspect of the present invention provides a battery, comprising the positive electrode material of the first aspect.

[0090] It is understood that in the present invention, the positive electrode material can be prepared into a positive electrode sheet using a method commonly used in the art, and then the positive electrode sheet and the negative electrode sheet are assembled to obtain a battery.

[0091] The battery of the present invention includes the positive electrode material of the first aspect and therefore has excellent charge and discharge capacity.

[0092] The technical solution of the present invention will be further explained below in conjunction with specific embodiments.

[0093] Example 1

[0094] The positive electrode material of this embodiment is prepared by a method comprising the following steps:

[0095] a. Weigh a sodium source, an iron source, a phosphorus source, a boron source, a M source, and a carbon source, and stir and dissolve them in deionized water to obtain a raw material system;

[0096] Among them, the mass percentage of the carbon source is 10%;

[0097] The sodium source is sodium iron pyrophosphate, the iron source is iron phosphate, the boron source is boron nitride, the M source is aluminum oxide, and the carbon source is glucose;

[0098] The total weight of the raw material system is 50 kg, and the solid content is 0.3 wt%;

[0099] b. Transfer the raw material system to a horizontal sand mill and perform sand milling for 250 minutes at a speed of 1500 rpm to obtain a spray slurry with a D50 of 0.28 to 0.3 μm;

[0100] c. spray drying the spray slurry to obtain spray particles with a D50 of 5 to 8 microns;

[0101] In the spray drying process, the inlet air temperature of the spray dryer was 185°C, the outlet air temperature was 85°C, and the feed speed was 35 rpm;

[0102] d. Use a sagger to collect the spray particles, transfer the spray particles to an atmosphere tube furnace, perform vacuum and nitrogen circulation operations three times, and set three temperature intervals to perform the first sintering treatment, the second sintering treatment, and the third sintering treatment respectively;

[0103] In the first sintering process, the temperature is 200°C and the time is 3h;

[0104] In the second sintering treatment, the temperature was 450°C and the time was 12 h;

[0105] In the third sintering treatment, the temperature was 550°C, the time was 5 h, and the heating rate of the tube furnace was 5°C / min;

[0106] e. The system after the third sintering treatment is transferred to a jet mill for crushing treatment; then drying, batch mixing, screening and iron removal treatment are carried out to finally obtain a positive electrode material. The specific parameters of the positive electrode material are shown in Table 1.

[0107] Example 2

[0108] The preparation method of the positive electrode material of this embodiment is basically the same as that of embodiment 1, except that:

[0109] In step a, the molar ratio of each element in the core is different from that in Example 1.

[0110] Example 3

[0111] The preparation method of the positive electrode material of this embodiment is basically the same as that of embodiment 1, except that:

[0112] In step d, the spray particles are loaded into a sagger, transferred into an atmosphere tube furnace, vacuumed and nitrogen-filled for four cycles, and four temperature intervals are set to perform a first sintering treatment, a second sintering treatment, a third sintering treatment, and a fourth sintering treatment respectively;

[0113] In the first sintering process, the temperature is 200°C and the time is 3h;

[0114] In the second sintering treatment, the temperature was 300°C and the time was 2 h;

[0115] In the third sintering treatment, the temperature is 450°C and the time is 12h;

[0116] In the fourth sintering treatment, the temperature is 550°C, the time is 5h, and the heating rate of the tube furnace is 5°C / min;

[0117] In step e, the system after the fourth sintering treatment is transferred to a jet mill for crushing treatment; and then dried, batch mixed, sieved and iron removed to finally obtain the positive electrode material.

[0118] Example 4

[0119] The preparation method of the positive electrode material of this embodiment is basically the same as that of embodiment 1, except that:

[0120] In step a, the sodium source and phosphoric acid are disodium dihydrogen phosphate, and the iron source is ferrous oxalate;

[0121] In step d, the second sintering treatment lasts for 8 hours;

[0122] The third sintering process lasts for 8 hours.

[0123] Example 5

[0124] The preparation method of the positive electrode material of this embodiment is basically the same as that of embodiment 1, except that:

[0125] In step c, the spray slurry is spray dried to obtain spray particles with a D50 of 8 to 9 microns;

[0126] In the spray drying process, the inlet air temperature of the spray dryer is 165°C, the outlet air temperature is 75°C, and the feed speed is 30 rpm.

[0127] Example 6

[0128] The preparation method of the positive electrode material of this embodiment is basically the same as that of embodiment 1, except that:

[0129] In step b, the raw material system is transferred to a horizontal sand mill and sand-milled at a speed of 1300 rpm for 180 minutes to obtain a spray slurry with a D50 of 0.3-0.35 μm;

[0130] In step c, the spray slurry is spray dried to obtain spray particles with a D50 of 9 to 10 microns;

[0131] In the spray drying process, the inlet air temperature of the spray dryer is 170°C, the outlet air temperature is 80°C, and the feed speed is 35 rpm.

[0132] Example 7

[0133] The preparation method of the positive electrode material of this embodiment is basically the same as that of embodiment 1, except that:

[0134] In step a, weighing a sodium source, an iron source, a phosphorus source, a boron source, a M source, and a carbon source, stirring and dissolving them in deionized water to obtain a raw material system;

[0135] The mass percentage of the carbon source is 8%.

[0136] Example 8

[0137] The preparation method of the positive electrode material of this embodiment is basically the same as that of embodiment 1, except that:

[0138] In step a, the M source is Mn 2 O 3 .

[0139] Comparative Example 1

[0140] The preparation method of the positive electrode material of this comparative example is basically the same as that of Example 1, except that:

[0141] In step a, the raw material system does not include a boron source.

[0142] Comparative Example 2

[0143] The preparation method of the positive electrode material of this comparative example is basically the same as that of Example 1, except that:

[0144] In step b, the D50 of the spray slurry is 10 μm;

[0145] In step c, the D50 of the sprayed particles is 30 μm.

[0146] Comparative Example 3

[0147] The preparation method of the positive electrode material of this comparative example is basically the same as that of Example 1, except that:

[0148] In step d, the spray particles are loaded into a sagger, transferred into an atmosphere tube furnace, vacuumed and nitrogen-filled for two cycles, and two temperature intervals are set to perform a first sintering treatment and a second sintering treatment respectively;

[0149] In the first sintering process, the temperature is 450°C and the time is 12h;

[0150] In the second sintering treatment, the temperature was 550° C., the time was 5 h, and the heating rate of the tubular furnace was 5° C. / min.

[0151] Comparative Example 4

[0152] The preparation method of the positive electrode material of this comparative example is basically the same as that of Example 1, except that:

[0153] In step d, the spray particles are loaded into a sagger, transferred into an atmosphere tube furnace, vacuumed and nitrogen-filled for two cycles, and two temperature intervals are set to perform a first sintering treatment and a second sintering treatment respectively;

[0154] In the first sintering process, the temperature is 200°C and the time is 3h;

[0155] In the second sintering treatment, the temperature was 550° C., the time was 5 h, and the heating rate of the tubular furnace was 5° C. / min.

[0156] Test example

[0157] The positive electrode materials in the embodiments or comparative examples are used to prepare batteries respectively, specifically comprising:

[0158] 1. Preparation of positive electrode

[0159] The positive electrode sheet includes an aluminum foil and a positive electrode active layer arranged on two functional surfaces of the aluminum foil;

[0160] The positive electrode active layer includes a positive electrode material, a conductive agent SP, a binder PVDF and oxalic acid, wherein the mass ratio of the positive electrode material, the conductive agent SP, the binder PVDF and the oxalic acid is 90:4.75:4.75:0.5.

[0161] 2. Preparation of negative electrode sheet

[0162] The negative electrode sheet includes a copper foil and a negative electrode active layer arranged on two functional surfaces of the copper foil;

[0163] The negative electrode active layer includes hard carbon, conductive agent SP and binder PVDF, and the mass ratio of hard carbon, conductive agent SP and binder PVDF is 3:3:94.

[0164] 3. Preparation of batteries

[0165] The positive electrode sheet and the separator in step 1 and the negative electrode sheet in step 2 are stacked to obtain an electrode assembly, and the electrode assembly is placed in an aluminum-plastic film and injected with commercially available NaPF 6 Electrolyte, get a battery.

[0166] Performance Testing

[0167] The following performance tests were performed on the positive electrode materials in the embodiments and comparative examples and the batteries in the test examples, and the results are shown in Tables 1-3;

[0168] 1. SEM-EDS test

[0169] Obtain the surface SEM image of the positive electrode material of Example 1, Figure 1 The surface SEM image of the positive electrode material in Example 1 of the present invention is shown in FIG. Figure 1 It can be seen that the primary particles of the NFPP positive electrode material can be evenly arranged to form a secondary particle structure, and no crystalline impurity structure appears.

[0170] The cross section of the positive electrode material of Example 1 was subjected to SEM-EDS testing to obtain a cross-sectional SEM image of the positive electrode material of Example 1 and the cross-sectional element distribution. Figure 2 This is a cross-sectional SEM image of the positive electrode material in Example 1 of the present invention; Figure 3 This is a cross-sectional SEM image of the positive electrode material in Comparative Example 3 of the present invention. Figure 2 and Figure 3 It can be seen that when only the secondary sintering treatment is performed, the carbon coating layer on the surface of the obtained positive electrode material is uneven. When the positive electrode material is used in a battery, the ion diffusion capacity is low, which is not conducive to the electrochemical performance of the battery.

[0171] Figure 4 This is a cross-sectional C element distribution diagram of the positive electrode material in Example 1 of the present invention; Figure 5 This is a cross-sectional Fe element distribution diagram of the positive electrode material in Example 1 of the present invention; Figure 6 This is a cross-sectional P element distribution diagram of the positive electrode material in Example 1 of the present invention; Figure 7 This is a cross-sectional Na element distribution diagram of the positive electrode material in Example 1 of the present invention; Figure 8 : is the cross-sectional B element distribution diagram of the positive electrode material in Example 1 of the present invention. Figure 4 It can be seen that in the positive electrode material obtained by the present invention, the carbon coating layer is uniformly coated on the surface of the core; Figure 5-8 It can be seen that in the positive electrode material of the present invention, the elements Na, Fe, P, and B are evenly distributed inside the secondary particles, indicating that the preparation method of the present invention can make the raw materials fully react, increase the content of NFPP in the inner core, and thus improve the capacity and structural stability of the positive electrode material.

[0172] 2. XRD test

[0173] XRD tests were performed on the positive electrode materials in the embodiment and the comparative example respectively to obtain the XRD patterns of the positive electrode materials, and then the XRD patterns were refined to obtain the a-axis length, b-axis length, c-axis length, and cell volume of the positive electrode materials in the unit cell of the positive electrode materials; the Na 4 Fe x (PO 4 ) 2 P 2 O 7 (NFPP), NaFePO 4 (NFP), Na 2 FeP 2 O 7 and NaFe(P 2 O 7 ) by weight, the results are shown in Table 2.

[0174] Fig. 9 This is the XRD diagram of the positive electrode material in Example 1 of the present invention.

[0175] 3. Charge and discharge specific capacity

[0176] The batteries prepared from the positive electrode materials in the embodiment and the comparative example were tested, and the theoretical capacity was 129 mAh / g, and the compaction density was controlled to be 1.8 g / cm 3 , 0.2C cycle, voltage range 2.0-4.0V.

[0177] Fig.10 The charge and discharge curves of the battery prepared by the positive electrode materials in the embodiments of the present invention and the comparative examples are shown in FIG. Fig.10 It can be seen that the positive electrode material of the embodiment of the present invention has better charge and discharge performance when applied to a battery.

[0178] 4. Ion diffusion coefficient

[0179] Assuming the positive electrode material to be a sphere with a diameter of Rs, the ion diffusion coefficient of the positive electrode material is obtained according to the following formula:

[0180]

[0181] Wherein, Ds is the diffusion coefficient; τ is the relaxation time (set to 15min, i.e. 900s); ΔVs is the total voltage change caused by the pulse, ΔVt is the voltage change of constant current charge and discharge, ΔVs and ΔVt are measured by setting the pulse test of the electrochemical workstation, and the particle size Rs of the positive electrode material is measured by the SEM image.

[0182] Fig.11 Graph showing the ion diffusion coefficient in the charging stage of the battery prepared with the positive electrode materials in Example 1 and Comparative Example 3 of the present invention. Fig.12 The ion diffusion coefficient curves of the battery prepared from the positive electrode materials in Example 1 and Comparative Example 3 of the present invention are shown in FIG. Figure 11-12 It can be seen that the positive electrode material obtained in the embodiment of the present invention has a more excellent ion diffusion coefficient when applied to a battery.

[0183] 5. Electrochemical impedance

[0184] The AC impedance of the battery was measured using an electrochemical workstation.

[0185] Fig.13 The electrochemical impedance spectra of the batteries in Example 1 and Comparative Example 3 of the present invention are shown in FIG. Fig.13 It can be seen that the battery prepared by the positive electrode material of the embodiment of the present invention has a lower electrochemical impedance.

[0186] 6. Cycle performance

[0187] Get the capacity retention rate of the battery after 600 cycles at 0.2C.

[0188] Table 1

[0189]

[0190]

[0191] Table 2

[0192]

[0193]

[0194] Table 3

[0195] Charge and discharge specific capacity Electrochemical impedance Cycle performance Example 1 <![CDATA[113.9mAh g -1 ]]> 0.122Ω 92.4% Example 2 <![CDATA[113.8mAh g -1 ]]> 0.117Ω 90.9% Example 3 <![CDATA[111.7mAh g -1 ]]> 0.125Ω 91.3% Example 4 <![CDATA[113.6mAh g -1 ]]> 0.112Ω 91.6% Example 5 <![CDATA[109.6mAh g -1 ]]> 0.129Ω 87.3% Example 6 <![CDATA[98.3mAh g -1 ]]> 0.118Ω 90.3% Example 7 <![CDATA[99.3mAh g -1 ]]> 0.153Ω 90.2% Example 8 <![CDATA[94.8mAh g -1 ]]> 0.113Ω 89.4% Comparative Example 1 <![CDATA[87.9mAh g -1 ]]> 0.159Ω 86.7% Comparative Example 2 <![CDATA[92.4mAh g -1 ]]> 0.147Ω 83.2% Comparative Example 3 <![CDATA[92.5mAh g -1 ]]> 0.143Ω 74.6% Comparative Example 4 <![CDATA[78.4mAh g -1 ]]> 0.183Ω 78.3%

[0196] It can be seen from Table 3 that when the positive electrode material in the embodiment of the present invention is applied to a battery, the charge and discharge specific capacity and cycle performance of the battery can be improved and the electrochemical impedance of the battery can be reduced, indicating that the positive electrode material of the present invention has excellent conductivity and stability.

[0197] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A positive electrode material, characterized in that: The positive electrode material comprises a core and a carbon coating layer coated on at least a portion of the surface of the core; The molecular formula of the core is shown in Formula 1; Na x Fe y M Z B a (PO4)2(P2O7) Formula 1; Wherein, M is a transition metal doping element; 3.8≤x≤4.2, 2.5≤y≤3, 0≤z≤0.5, 0.00001≤a≤0.0005; The phase composition of the inner core includes Na4Fe x (PO4)2P2O7, NaFePO4, Na2FeP2O7 and NaFe(P2O7), and in the phase composition of the core, Na4Fe x The mass percentage of (PO4)2P2O7 is ≥89%, the mass percentage of NaFePO4 is 1-8%, the mass percentage of Na2FeP2O7 is 2-9%, and the mass percentage of NaFe(P2O7) is 0.2-1.5%; In the positive electrode material, the mass percentage of the carbon coating layer is 1-5%.

2. The positive electrode material according to claim 1, characterized in that The moisture content of the positive electrode material is ≤1000ppm.

3. The positive electrode material according to claim 1 or 2, characterized in that The D50 of the positive electrode material is 2-15 μm.

4. The positive electrode material according to any one of claims 1 to 3, characterized in that The thickness of the carbon coating layer is 3-4 nm.

5. The positive electrode material according to any one of claims 1 to 4, characterized in that In the unit cell of the positive electrode material, the length of the a-axis is The length of the b axis is The length of the c-axis is and / or, The unit cell volume of the positive electrode material is 6. A method for preparing the positive electrode material according to any one of claims 1 to 5, characterized in that: The following steps are involved: A raw material system including a sodium source, an iron source, a carbon source, a boron source, and a phosphorus source or a raw material system including a sodium source, an iron source, a carbon source, a boron source, a phosphorus source, and an M source is subjected to sand milling to obtain a spray slurry having a D50 of 0.25-0.35 μm; The spray slurry is spray-dried to obtain spray particles with a D50 of less than 10 μm; Sintering the spray particles to obtain the positive electrode material; The sintering process at least includes a first sintering process, a second sintering process, and a third sintering process, and the temperature of the first sintering process, the temperature of the second sintering process, and the temperature of the third sintering process increase in sequence.

7. The preparation method according to claim 6, characterized in that: In the first sintering treatment, the temperature is 160-200° C. and the time is 2-5 hours; and / or, In the second sintering treatment, the temperature is 430-500° C. and the time is 10-16 hours; and / or, In the third sintering treatment, the temperature is 520-580° C. and the time is 2-6 hours.

8. The preparation method according to any one of claims 6 to 7, characterized in that: In the sand grinding process, the sand grinding speed is 1200-1600 r / min and the time is 250-400 min.

9. The preparation method according to any one of claims 6 to 8, characterized in that: In the spray drying process, the inlet air temperature is 170-190°C, and the outlet air temperature is 80-100°C.

10. A battery, characterized in that: The positive electrode material comprises the positive electrode material according to any one of claims 1 to 5.

Citation Information

Cited By

  • Positive electrode material, and preparation method therefor and use thereof

    WO2026144109A1